Systematic Literature Review : Pengembangan Model Smart Community-Based Management dalam Pengelolaan PAUD untuk Meningkatkan Kualitas Layanan, Partisipasi Orang Tua, dan Tata Kelola Kelembagaan - Anita, Adela; Cahyanengdian, Asri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to develop a conceptual model of Smart Community-Based Management (SCBM) in Early Childhood Education (ECE/PAUD) through a Systematic Literature Review (SLR) approach. The review synthesizes existing literature related to institutional governance, Community-Based Management, parental involvement, Smart Management and Digital Governance, and ECE service quality. The study follows the PRISMA guidelines to ensure a systematic, transparent, and replicable process of article identification, screening, eligibility, and inclusion. The findings indicate that ECE management still faces several challenges, including weak integration of institutional governance, suboptimal community participation, limited parental involvement in decision-making processes, and the restricted use of digital technology primarily for administrative purposes. On the other hand, Community-Based Management enhances accountability and community ownership, while Smart Management and Digital Governance strengthen data-driven decision-making, transparency, and educational service efficiency. Based on the synthesis of the reviewed literature, this study proposes the SCBM model, which integrates institutional governance, community participation, parental engagement, and digital transformation into a collaborative, adaptive, and data-driven ECE management system. The model is expected to improve the quality of ECE services through stronger synergy among schools, families, communities, and technology, particularly in geographically challenging regions such as South Papua..